Harnessing the photoelectrochemical properties of BiSI nanorods towards the degradation of norfloxacin in water - Babatunde A. Koiki; Omotayo A. Arotiba (Applied Catalysis O: Open)
The increasing demand for a low cost and sustainable technology towards the production of reactive oxidants for water treatment continues to draw the attention of researchers. Photoelectrochemical (PEC) technology remains a promising approach because of the synergistic effects arising from both photocatalytic and electrochemical techniques. In this work, bismuth sulphur iodide (BiSI) nanorods were prepared and characterised with XRD, FESEM, TEM, and UV-DRS. The photoelectrochemical properties of the BiSi nanorods were studied using linear sweep voltammetry, cyclic voltammetry, electrochemical impedance spectroscopy, and Mott-Schottky measurements. The properties of BiSI nanorods were harnessed towards the generation of reactive oxidants for the degradation of norfloxacin in water. When the BiSI photocatalyst was applied for the degradation of norfloxacin, the photocatalytic (PC), electrochemical (EC), and photoelectrochemical (PEC) techniques achieved 31 %, 65 %, and 88 % degradation, respectively. Also, the versatility of BiSI nanorods photoanode in a PEC system achieved a 95 % degradation of 4-nitrophenol within 180 min, as well as a 100 % degradation of orange II dye within 60 min. Scavenger studies revealed that reactive oxidants such as holes, hydroxyl radicals, and superoxides participated in the degradation process. The electrode was found to be stable and can be applied for the degradation of other pharmaceutical pollutants in a PEC degradation system. Overall, the mechanism of nofloxacin degradation was presented based on the intermediate products identified using UPLC-MS and the level of toxicity was estimated using quantitative structure activity relationship (QSAR) analysis.